FAKTOR PENENTU KETERLIBATAN GENERASI MUDA DALAM PERTANIAN TANAMAN PANGAN (Kasus: Nagari Desa Baru, Kecamatan Ranah Batahan, Kabupaten Pasaman Barat, Sumatera Barat) - Ghina faridah (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2020)
ABSTRACTThe phenomenon of aging farmers is a concern of Indonesia and other countries. Indonesia faces the problem of decreasing the number of young agricultural workers. There are many reasons behind the younger generation who do not want to work in the agricultural sector, including the image of the agricultural sector which is less prestigious and unable to provide adequate appreciation and the perspective of young workers that has changed in the postmodern era. On the other hand, there are some young people who are motivated and interested in becoming young farmers. The purpose of this study was to analyze the determinants of young generation involvement in food crop agriculture. The factors analyzed are internal factors and external factors. Internal factors include education, farming experience, gender, marital status, and motivation to become a farmer. Meanwhile, external factors include the main activities of parents, support from parents, parental land parcels, community support, and technology. This research was conducted using quantitative and qualitative methods. The results of this study indicate that there are four factors that have a significant effect on the involvement of the younger generation in food crop agriculture, namely: education, farming experience, motivation to become a farmer, and parental support. Keywords: Young farmers, agrarian structure, food crops ABSTRAKFenomena aging farmer atau penuaan petani sudah menjadi perhatian Indonesia dan negara-negara lainnya. Indonesia menghadapi permasalahan menurunnya jumlah tenaga kerja muda pertanian. Banyak alasan yang mendasari generasi muda tidak mau bekerja disektor pertanian, diantaranya adalah citra sektor pertanian yang kurang bergengsi dan kurang bisa memberikan imbalan memadai dan cara pandang tenaga kerja muda telah berubah di era perkembangan masyarakat post modern. Disisi lain, terdapat generasi muda yang termotivasi dan berminat menjadi petani muda. Tujuan dari penelitian ini untuk menganalisis faktor penentu keterlibatan generasi muda dalam pertanian tanaman pangan. Faktor yang dianalisis berupa faktor internal dan eksternal. Faktor Internal meliputi pendidikan, pengalaman bertani, jenis kelamin, status pernikahan, dan motivasi menjadi petani. Sedangkan, faktor eksternal meliputi aktivitas utama orangtua, dukungan orangtua, luas pengasaan lahan orang tua, dukungan masyarakat dan teknologi. Penelitian ini dilakukan dengan metode kuantitatif dan kualitatif. Hasil penelitian ini menunjukkan bahwa terdapat empat faktor yang signifikan mempengaruhi keterlibatan generasi muda dalam pertanian tanaman pangan diantaranya adalah: pendidikan, pengalaman bertani, motivasi untuk menjadi petani dan dukungan orang tua. Kata Kunci: Petani muda, struktur agraria, tanaman pangan